Subjective Cognitive Decline in Older Adults: An Overview of Self-Report Measures Used Across 19 International Research Studies. - Rabin, L. A.; Smart, C. M.; Crane, P. K.; Amariglio, R. E.; Berman, L. M.; Boada, M.; Buckley, R. F.; Chetelat, G.; Dubois, B.; Ellis, K. A.; Gifford, K. A.; Jefferson, A. L.; et al. (J Alzheimers Dis, 2015)
Research increasingly suggests that subjective cognitive decline (SCD) in older adults, in the absence of objective cognitive dysfunction or depression, may be a harbinger of non-normative cognitive decline and eventual progression to dementia. Little is known, however, about the key features of self-report measures currently used to assess SCD. The Subjective Cognitive Decline Initiative (SCD-I) Working Group is an international consortium established to develop a conceptual framework and research criteria for SCD (Jessen et al., 2014, Alzheimers Dement 10, 844-852). In the current study we systematically compared cognitive self-report items used by 19 SCD-I Working Group studies, representing 8 countries and 5 languages. We identified 34 self-report measures comprising 640 cognitive self-report items. There was little overlap among measures- approximately 75% of measures were used by only one study. Wide variation existed in response options and item content. Items pertaining to the memory domain predominated, accounting for about 60% of items surveyed, followed by executive function and attention, with 16% and 11% of the items, respectively. Items relating to memory for the names of people and the placement of common objects were represented on the greatest percentage of measures (56% each). Working group members reported that instrument selection decisions were often based on practical considerations beyond the study of SCD specifically, such as availability and brevity of measures. Results document the heterogeneity of approaches across studies to the emerging construct of SCD. We offer preliminary recommendations for instrument selection and future research directions including identifying items and measure formats associated with important clinical outcomes.
Keywords: Aged; Aged, 80 and over; Aging/*psychology; Cognition Disorders/*diagnosis/epidemiology/*psychology; Executive Function; Female; Humans; Male; Multicenter Studies as Topic; Neuropsychological Tests; Psychiatric Status Rating Scales; *Self Report; Surveys and Questionnaires